Current challenges of the European security caused by the refugee crisis. The EU's fight against terrorism - Andreea Florentina Nicolescu (CES Working Papers, 2017)
The primary objective of this research is to identify the evolution of the terrorist attacks that appeared in Europe lately. In the article are mentioned the main causes that led to the terrorist attacks from France and Germany, emphasizing their effects over the 2 countries. The article brings forward the main types of attacks used by terrorists but also the number of injured persons or deaths. An essential aspect that was highlighted in the article refers to the results obtained after applying the EU – Turkey Statement but also to those regarding the transfer and relocation of the migrants in different countries. In this way, the analysis implied the selection of EU member states which received Syrian refugees by relocation together with the highlighting of the numeric situation of the persons returned from Greece to Turkey. A last part of this study assumes the identification of the personal categories who have been brought by Frontex and EASO in Greece in order to handle efficiently the crisis, which provide the expertise in the migration field. The primary question of this research is: “Is EU capable to administer the changes regarding migration, assuring in the same time its safety?”. To answer this question, I identified first the costs of EU securitizing its states. I consider that the approach of this matter has a high importance since it shows the necessity of some changes meant to help European states to face the events linked to migration and, implicitly, security from the last years.
Keywords: 330; refugee crisis; terrorism; security challenges; migration